Fostering Cultural Harmony: Economic Empowerment of Ethnic Chinese within the Minangkabau Philosophical Framework in Padang City - Cahya, Bayu Tri; Sukardi, Agung Slamet; Andriasari, Widi Savitri; Atieq, Muhammad Qoes; Ali, Nor Aishah Mohd (IQTISHADIA, 2024)
This study explores the intersection of cultural beliefs and spatial dynamics shaping the economic activities of the ethnic Chinese community in Padang City, focusing on their empowerment through Minangkabau traditional philosophy. The research highlights how cultural values deeply influence identity, social interactions, and economic opportunities within a pluralistic society. A qualitative ethnographic approach was used to gather insights from key community members, including Minangkabau and non-Minangkabau residents, as well as the Tungku Tigo Sajarangan, which consists of ninik mamak (tribal leaders), alim ulama (religious scholars), and cadiak pandai (intellectuals). Interviews centered on cultural and economic integration, exploring how traditional Minangkabau norms intersect with ethnic Chinese values. The research reveals that the Minangkabau traditional philosophy fosters an environment of coexistence, allowing the ethnic Chinese community to practice their cultural traditions without violating the overarching norms of "Adat Basandi Syarak, Syarak Basandi Kitabullah”. This cultural harmony supports economic engagement while respecting Confucian principles, which coexist with Minangkabau values. This study broadens the discourse on multiculturalism and economic interactions by highlighting how Minangkabau and Confucian values coexist within a shared economic and cultural space. The research provides new insights into the role of traditional philosophy in fostering economic inclusivity.